ANALISIS FAKTOR YANG BERPENGARUH TERHADAP PERTUMBUHAN EKONOMI DAN KUALITAS SDM DI KABUPATEN/KOTA PROVINSI BALI - A.A.I.N Marhaeni, Putu Dina Kartika Sari, (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 8 No 10 (2019): Vol. 8, No. 10, Oktober 2019, pp [2195 - 2500], 2019)
The purpose of this research was to analyze 1) the influence of labor and investment on economic growth in the regency/city of Bali Province; 2) analyze the influence of labor, investment and economic growth on the quality of human resources in the regency/city of Bali Province; 3) analyze the role of economic growth in mediating the influence of labor work and investment in the quality of human resources in the regency/city of Bali Province. This research was conducted in Bali Province using eight regency and one city as their observation points, with a period of 2011 to 2015 the sample size was 45 observations using panel data. The data analysis technique used is quantitative analysis techniques, namely path analysis. The results of path analysis show that labor and investment directly have significant positive effect on economic growth in the regency/city of Bali Province. Labor, investment and economic growth directly have significant positive effect on the quality of human resources, especially in the human development index in the regency/city of Bali Province. Economic growth partially mediates the influence of labor and investment on the human development index in the regency/city of Bali Province.   Keywords : labor, investment, economic growth, human development index.